Perspektif Gender: Faktor-faktor Penentu Prestasi Akademik Mahasiswa Akuntansi - Azis, Siti Nafisah (Program Studi Akuntansi FPEB UPI, 2021)
Abstract. This study aims to examine the factors that influence academic achievement of accounting student consisting of intellectual intelligence, emotional intelligence, spiritual intelligence, learning behavior, lecturer competence, and educational facilities, and examine the differences in the levels of intellectual intelligence, emotional intelligence, spiritual intelligence, learning behavior, and academic achievements based on gender. The research subjects were students majoring in accounting at Politeknik Negeri Ujung Pandang. The sample collection method was purposive sampling that generate total sample of 73 students.The research data consisted of primary data obtained through online questionnaires and secondary data in the form of student GPA. The analysis method used was multiple regression analysis and independent sample t-test. The results showed that emotional intelligence and learning behavior had a positive effect on the academic achievement of accounting students. Intellectual intelligence, spiritual intelligence, learning behavior, lecturer competence, and educational facilities had no effect on the academic achievements of accounting students. This research also proved that there was no significant difference between the level of intelligence (intellectual, emotional, spiritual), learning behavior, and academic achievement between male and female students. Abstrak. Penelitian ini bertujuan untuk menguji faktor-faktor yang memengaruhi prestasi akademik mahasiswa akuntansi yang terdiri atas kecerdasan intelektual, kecerdasan emosional, kecerdasan spiritual, perilaku belajar, kompetensi dosen, dan sarana pendidikan, dan menguji perbedaan tingkat kecerdasan intelektual, kecerdasan emosional, kecerdasan spiritual, perilaku belajar, dan prestasi akademik berdasarkan gender. Subjek penelitian adalah mahasiswa jurusan akuntansi Politeknik Negeri Ujung Pandang. Metode pengumpulan sampel adalah purposive sampling, sehingga diperoleh sampel sebanyak 73 mahasiswa. Data penelitian terdiri atas data primer yang diperoleh melalui kuesioner online dan data sekunder yang berupa IPK mahasiswa. Metode analisis data menggunakan analisis linear berganda dan uji beda independent t-test. Hasil penelitian menunjukkan bahwa kecerdasan emosional dan perilaku belajar berpengaruh positif terhadap prestasi akademik mahasiswa akuntansi. Kecerdasan intelektual, kecerdasan spiritual, perilaku belajar, kompetensi dosen, dan sarana pendidikan tidak berpengaruh terhadap prestasi akademik mahasiswa. Penelitian ini juga membuktikan bahwa tidak terdapat perbedaan yang signifikan antara tingkat kecerdasan (intelektual, emosional, spiritual), perilaku belajar, dan prestasi akademik antara mahasiswa laki-laki dan perempuan.